PEMAKNAAN PERUBAHAN PUSKESMAS X MENUJU BADAN LAYANAN UMUM DAERAH (BLUD) DALAM ASPEK LAYANAN DAN AKUNTANSI - Rizda Yuritsuni Firdausi; Sri Pujiningsih (Jurnal Akuntansi Aktual, 2018)
This research aims to understand the giving of meaning by the actors in Puskesmas X about Puskesmas X’s organizational change towards BLUD viewed from the aspect of service and accounting. This research is a phenomenology using case study as the research strategy. This research took place in Puskesmas X. The research data were generated from interviewing the research informants. The research informants are The Head of Puskesmas X, Puskesmas X’s chamberlains, and medical staff. The results of this research show that the Puskesmas X’s actors who indirectly participate in making financial reports tend to accept BLUD, while the actors who directly participate in making financial reports tend to resist BLUD.